The Application of Transformational Leadership and Work Discipline to the Performance of Seskoal Soldiers in Jakarta - Jales Jamca Jayamahe; Anita Kartika Sari; Sri Rahayu (Jurnal Kewarganegaraan, 2024)
Abstract Most soldiers are less than optimal in effectiveness, efficiency, and agility, as seen from delays and lags in completing tasks and submitting activity reports. The research location is at Seskoal, Cipulir, South Jakarta. The purpose of this study was to determine the application of transformational leadership and work discipline to the performance of Seskoal soldiers in Jakarta. The research method used is qualitative with data collection techniques through observation, in-depth interviews, and content analysis. The results showed that the application of transformational leadership by the Seskoal Commander encourages staff to prioritize the interests of the organization, so that the goals set can be achieved. In addition, the application of wise and fair work discipline also has a positive impact on the productivity, safety, welfare, and overall success of the institution. Thus, both factors have an important role in improving the performance of Seskoal soldiers. Keywords: Leadership, Work Discipline, Performance, Seskoal Soldiers. Keywords: Leadership; Work Discipline; Performance; Seskoal Soldiers